Análisis jurídico sobre las causas y consecuencias derivados de la falta de sanción al peatón infractor por lo inobservancia de la ley orgánica de trasporte terrestre, tránsito y seguridad vial, ciudad de Arenillas, en el periodo 2012 - Barrionuevo Ramírez, Felipe Benancio (2014)
It is therefore that it emerges as an initiative of the group to be able to develop the present investigation with the aim of being able to give a legal solution and thus contribute with society, since it constitutes a problem of relevance in the city of Arenillas, Which places a latent risk on the most prized legal good as the right to life.